A huge epidermal inclusion cyst of the vulva complicating neonatal female circumcision (Indian Journal of Case Reports, 2019)
Female genital mutilation is the summation of all procedures that involve partial or total removal of the female external genitalia or other injuries to the female genital organs, whether for cultural or other non-therapeutic reasons. Hemorrhage, sepsis and genitourinary damage are the main early causes of morbidity and occasional mortality associated with this practice. Vulva epidermal inclusion cysts, sexual and birth difficulties occur late and can cause medical, psychological and socioeconomic problems. Here, we present the case of a 42-year-old circumcised female, who presented with a huge vulva swelling of 30 years duration that posed some diagnostic challenge because of the presence of other body swellings arising from neurofibromatosis. This was successfully excised and histology showed it was epidermal inclusion cyst, which we believed was a late complication of her neonatal circumcision.